Hollywood and the representation of the Otherness. A historical analysis of the role played by movies in spotting enemies to vilify - Gelado Marcos, Roberto (2016)
Hollywood has played a decisive role in shaping the recent and short history of its founding country, the United States. This paper aims at exploring the representation of peoples outside the Western standard in Hollywood movies to spot recurrences in portraying Others, especially in vilifying terms. The analysis of plots and characters in American movies in different historical stages reveal not only consistent patterns in the depiction of Otherness, but also an even more interesting need to define and reaffirm the Self through the opposition to changing Others that mainly depend on the historical and political period occurring.